A new cerium iodate infrared nonlinear optical material with a large second-harmonic generation response. Issue 8 (10th February 2017) - Xiao, Lei; Cao, Zhenbo; Yao, Jiyong; Lin, Zheshuai; Hu, Zhanggui
Abstract : A new rare earth ternary iodate, Ce2 I6 O18, has been synthesized by a high temperature hydrothermal method with homemade alloy reactor equipment. Abstract : A new rare earth ternary iodate, Ce2 I6 O18, has been synthesized by a high temperature hydrothermal method with homemade alloy reactor equipment. It crystallizes in the monoclinic system space group P 21 with a = 8.7252(2) Å, b = 7.0474(1) Å, c = 13.096(3) Å, β = 90.81(0)°, Z = 2, and V = 805.2(3) Å 3 . The material exhibits a three dimensional structure consisting of unlimited extending CeO9 polyhedrons and IO3 triangular pyramidal bilayers connected by I⋯O long bonds. The electronic band structure and optical properties of Ce2 I6 O18 were studied. It belongs to the type I phase-matchable class with an IR cutoff wavelength of 12.2 μm and second-harmonic generation (SHG) response of about 9 × KH2 PO4 (KDP).